The Hicks' Concept of Income and Its Relevancy for Accounting Purposes - David Procházka (European Financial and Accounting Journal, 2009)
The paper analyses the possibility of using the economic concept of income introduced by J. R. Hicks for accounting purposes. Despite some disadvantages hindering from its broader practical utilization, this concept still finds its place in the area of managerial accounting and capital maintenance. Some aspects of Hicks' income concepts can be even found in International Financial Reporting Standards.
Keywords: M41; 650; J. R. Hicks; Ex-ante income; Ex-post income; Subjective value; Subjective goodwill; Subjective profit